Antibacterial LED-UV curing rotary red ink
By using spherical nanozirconium dioxide with porous structures and functional additives in offset printing inks, the antibacterial envelope layer is solved, and the wear resistance and service life are improved.
Patent Information
- Application Number
- CN202411569962.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing offset printing ink has poor antibacterial properties and is prone to breeding bacteria, affecting its service life and quality.
A spherical nanozirconium dioxide with a porous structure is used as an inorganic substrate, and a dense three-dimensional antibacterial envelope layer is constructed on its surface through chemical reactions, and antibacterial LED-UV cured rotary red ink is prepared.
It significantly enhances the antibacterial properties of the ink, and improves wear resistance through the porous structure, extends service life, and ensures the quality of the ink.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing inks, in particular to an antibacterial LED-UV curing rotary red ink. Background Art
[0002] Offset printing is the most important printing method at present. Its characteristic is that fountain solution is needed in the printing process, so offset printing ink is required to have good water resistance. In the past, the binder of offset printing ink was mainly vegetable oil such as linseed oil, but now most of them have been replaced by various resins with better performance. Common resins include rosin-modified phenolic resin, alkyd resin and polyurethane alkyd resin.
[0003] An ink composition is disclosed in the patent document with application number "CN202310078731.7". The ink composition includes an optically variable pigment and a binder, the binder includes a photosensitive resin, an acrylic monomer and a photoinitiator, wherein the surface of the optically variable pigment is lipophilically treated with a treating agent, and the treating agent is configured to make the oil absorption of the optically variable pigment be 25g / 100g to 75g / 100g. Although the ink composition provided in this patent document has the advantages of good transfer rate, high printing stability and obvious angular color effect of the printed pattern, its antibacterial performance is relatively poor and it is easy to breed bacteria, which affects its service life to a certain extent, and also affects its quality. Therefore, the present invention provides an antibacterial LED-UV curing rotary red ink to solve the above-mentioned technical problems! Summary of the invention
[0004] The object of the present invention is to provide an antibacterial LED-UV curing rotary red ink, which not only has excellent antibacterial properties, but also has excellent wear resistance, effectively ensuring its quality and grade while also extending its service life to a certain extent.
[0005] To achieve the above object, the present invention provides the following technical solutions: An antibacterial LED-UV curing rotary red ink is composed of the following raw materials in weight percentage: 20-25% organic monomer, 8-10% photoinitiator, 0.3-0.8% tris(N-nitroso-N-phenylhydroxylamine)aluminum salt, 1-2% polyethylene wax, 5-8% functional additive, 1.5-2.5% dispersant, 12-15% red pigment, 0.6-1.2% drier, and the balance is a connecting material; wherein the red pigment is selected from any one of magenta 4B, magenta 6B, magenta 8B, and litho red; and the dispersant is selected from polyester polyamide copolymer.
[0006] Furthermore, the preparation method of the functional additive comprises the following steps: Step 1, cyanuric chloride, pretreated inorganic carrier, N, N-diethylethylamine and mixed solvent are mixed in a mass ratio of 1.5-2.0:1:0.02-0.04:8-12, 2,6-dimethyl-2,6-octadienal in a mass of 0.1-0.2 times that of the pretreated inorganic carrier is added, the mixture is stirred evenly, and the mixture is stirred and reacted at a temperature of 45-55° C. for 3-5 hours; after the reaction is completed, the resultant components are separated into solid and liquid, and the obtained filter cake is washed with anhydrous ethanol and deionized water for 3-5 times respectively; then vacuum dried, and the obtained solid powder is stored and used for standby; wherein the mixed solvent is prepared by mixing DMF and anhydrous ethanol in a volume ratio of 2-3:1.
[0007] Step 2: Mix 1,3-benzenediol, solid powder, aluminum chloride and chlorobenzene in a mass ratio of 1.3-1.8:1:0.03-0.05:7-10, stir evenly, keep stirring at 30-40°C for 30-40 minutes, then raise the reaction temperature to 90-95°C, continue to keep stirring for 5-8 hours, and then filter. Wash the filter cake with anhydrous ethanol and deionized water for 3-5 times, respectively, and then vacuum dry it. The final product is a functional additive.
[0008] Furthermore, the preparation method of the pretreated inorganic carrier is: add a modifying liquid with a mass 5 to 10 times that of the inorganic carrier to a 0.01 to 0.03 g / mL inorganic carrier ethanol dispersion, and keep stirring the reaction at a temperature of 50 to 60°C for 2 to 4 hours; after the reaction is completed, centrifuge the resulting components, wash the filter cake with anhydrous ethanol for 3 to 5 times and then transfer it to a vacuum drying device, and finally vacuum dry it at a temperature of 50 to 60°C to obtain the pretreated inorganic carrier.
[0009] Furthermore, the preparation method of the inorganic carrier is as follows: zirconium oxychloride is added into an ethanol aqueous solution with a volume concentration of 60-70% at a solid-liquid ratio of 30-80 mg / mL, methyl cellulose with a mass of 1.5-2 times that of zirconium oxychloride and polystyrene microspheres with an average particle size of 5-10 μm with a mass of 0.3-0.4 times that of zirconium oxychloride are added, the pH is adjusted to 3.2-3.8, and the reaction is stirred at a temperature of 40-50°C for 50-80 minutes; after the reaction is completed, the pH is adjusted to 5.5-5.8, and after aging at room temperature for 20-25 hours, the resulting components are centrifuged, dried and sintered at high temperature in sequence, and the final product is the inorganic carrier.
[0010] Furthermore, the preparation method of the modified liquid is: adding 3-aminopropyltrimethoxysilane to an ethanol aqueous solution with a volume concentration of 80-90%, mixing and stirring evenly to prepare a silane coupling agent aqueous solution with a concentration of 0.5-1.0 mol / L; then adjusting its pH to 3.5-3.8, and mixing and stirring at a rate of 200-500 r / min for 30-40 minutes at room temperature, and the modified liquid is obtained after the stirring is completed.
[0011] Furthermore, the temperature of the high temperature sintering is set to 1100-1150° C., and the sintering time is set to 1-2 hours.
[0012] Furthermore, the connecting material is compounded by vinyl ester resin and lauryl acrylate in a mass ratio of 1:0.8 to 1.0.
[0013] Furthermore, the photoinitiator is selected from any one of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide, bis (2,4,6-trimethylbenzoyl) phenyl phosphine oxide, and 3-methyl-4-phenyl benzophenone.
[0014] Furthermore, the organic monomer is selected from any one of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate.
[0015] Furthermore, the drying agent is selected from any one of cobalt isooctanoate, zirconium isooctanoate and calcium isooctanoate.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, zirconium oxychloride, methyl cellulose and polystyrene microspheres are used as raw materials to prepare spherical nano zirconium dioxide with a porous structure, i.e., an inorganic substrate. Then, the inorganic substrate is put into ethanol, and a modified liquid containing 3-aminopropyltrimethoxysilane is added to the ethanol dispersion, and the 3-aminopropyltrimethoxysilane reacts chemically with the active groups on the surface of the inorganic carrier through heat preservation and stirring reaction, and finally a pretreated inorganic carrier is prepared. The obtained pretreated inorganic carrier is mixed with cyanuric chloride, N,N-diethylethylamine and a mixed solvent, and 2,6-dimethyl-2,6-octadienal is added, and finally 2,6-dimethyl-2,6-octadienal is successfully grafted on the surface of the pretreated inorganic substrate under the medium of 3-aminopropyltrimethoxysilane, and the introduction of 2,6-dimethyl-2,6-octadienal effectively enhances the antibacterial properties of the prepared solid powder.
[0017] The obtained solid powder is then mixed with 1,3-benzenediol, aluminum chloride and chlorobenzene, and the 1,3-benzenediol reacts chemically with cyanuric chloride bonded to the surface of the solid powder and its porous structure through heat preservation and stirring reaction. Finally, the two react chemically, and the generated reaction product is effectively encapsulated on the surface of the solid powder, and cooperates with 2,6-dimethyl-2,6-octadienal, and finally a dense three-dimensional antibacterial encapsulation layer is constructed on the surface of the solid micropowder and the inside of the porous structure to obtain a functional additive. The prepared functional additive can be used as a raw material for rotary red ink to significantly enhance its antibacterial properties. Furthermore, since the inorganic substrate is a nano zirconium dioxide with a porous spherical structure, its spherical structure can also enhance the wear resistance of the obtained red ink product to a certain extent, effectively ensuring its quality while also extending its service life. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0019] An antibacterial LED-UV curing rotary red ink is composed of the following raw materials in percentage by weight: 20% 1,6-hexanediol diacrylate, 8% 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, 0.3% tris (N-nitroso-N-phenylhydroxylamine) aluminum salt, 1% polyethylene wax, 5% functional additives, 1.5% polyester polyamide copolymer, 12% litho red, 0.6% cobalt isooctanoate, and the balance is a connecting material; wherein the connecting material is compounded by vinyl ester resin and lauryl acrylate in a mass ratio of 1:0.8.
[0020] The preparation method of the functional additive comprises the following steps: Step 1, cyanuric chloride, pretreated inorganic carrier, N, N-diethylethylamine and mixed solvent are mixed in a mass ratio of 1.5:1:0.02:8, 2,6-dimethyl-2,6-octadienal is added in a mass of 0.1 times that of the pretreated inorganic carrier, the mixture is stirred evenly, and the mixture is stirred and reacted at a temperature of 45°C for 3 hours; after the reaction is completed, the resultant components are separated into solid and liquid, and the obtained filter cake is washed with anhydrous ethanol and deionized water for 3 times respectively; then vacuum dried, and the obtained solid powder is stored and used for standby; wherein the mixed solvent is prepared by mixing DMF and anhydrous ethanol in a volume ratio of 2:1.
[0021] Step 2: Mix 1,3-benzenediol, solid powder, aluminum chloride and chlorobenzene in a mass ratio of 1.3:1:0.03:7 and stir evenly. Keep stirring at 30°C for 30 minutes and then raise the reaction temperature to 90°C. Keep stirring for 5 hours and then filter. Wash the filter cake with anhydrous ethanol and deionized water for 3 times and then vacuum dry it. The final product is a functional additive.
[0022] The preparation method of the pretreated inorganic carrier is as follows: add a modifying liquid with a mass 5 times that of the inorganic carrier to a 0.01 g / mL inorganic carrier ethanol dispersion, and stir and react at a temperature of 50°C for 2 hours; after the reaction is completed, centrifuge the resulting components, wash the filter cake with anhydrous ethanol 3 times and then transfer it to a vacuum drying device, and finally vacuum dry it at a temperature of 50°C to obtain the pretreated inorganic carrier.
[0023] The preparation method of the inorganic carrier is as follows: zirconium oxychloride is put into an ethanol aqueous solution with a volume concentration of 60% at a solid-liquid ratio of 30 mg / mL, methyl cellulose with a mass of 1.5 times that of zirconium oxychloride and polystyrene microspheres with an average particle size of 5 μm with a mass of 0.3 times that of zirconium oxychloride are added, the pH is adjusted to 3.2, and the reaction is kept stirring at 40°C for 50 minutes; after the reaction is completed, the pH is adjusted to 5.5, and after aging at room temperature for 20 hours, the resulting components are centrifuged, dried and sintered at high temperature in sequence, and the final product is the inorganic carrier; wherein the high-temperature sintering temperature is set to 1100°C, and the sintering time is set to 1 hour.
[0024] The preparation method of the modified liquid is as follows: 3-aminopropyltrimethoxysilane is added to an ethanol aqueous solution with a volume concentration of 80%, and the mixture is mixed and stirred evenly to prepare a silane coupling agent aqueous solution with a concentration of 0.5 mol / L; then the pH thereof is adjusted to 3.5, and the mixture is mixed and stirred at a rate of 200 r / min for 30 minutes at room temperature, and the modified liquid is obtained after the stirring is completed. Example 2
[0025] An antibacterial LED-UV curing rotary red ink is composed of the following raw materials in percentage by weight: 20% trimethylolpropane triacrylate, 9% bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 0.5% tri(N-nitroso-N-phenylhydroxylamine)aluminum salt, 1.5% polyethylene wax, 6% functional additives, 2.0% polyester polyamide copolymer, 14% litho red, 1.0% zirconium isooctanoate, and the balance is a connecting material; wherein the connecting material is compounded by vinyl ester resin and lauryl acrylate in a mass ratio of 1:0.9.
[0026] The preparation method of the functional additive comprises the following steps: Step 1, cyanuric chloride, pretreated inorganic carrier, N, N-diethylethylamine and mixed solvent are mixed in a mass ratio of 1.8:1:0.03:10, 2,6-dimethyl-2,6-octadienal is added in a mass of 0.15 times that of the pretreated inorganic carrier, the mixture is stirred evenly, and the mixture is stirred and reacted at a temperature of 50°C for 4 hours; after the reaction is completed, the resultant components are separated into solid and liquid, and the obtained filter cake is washed 4 times with anhydrous ethanol and deionized water respectively; then vacuum dried, and the obtained solid powder is stored and used for standby use; wherein the mixed solvent is prepared by mixing DMF and anhydrous ethanol in a volume ratio of 2:1.
[0027] Step 2: Mix 1,3-benzenediol, solid powder, aluminum chloride and chlorobenzene in a mass ratio of 1.5:1:0.04:8 and stir evenly. Keep stirring at 35°C for 35 minutes and then raise the reaction temperature to 90°C. Keep stirring for 6 hours and then filter. Wash the filter cake with anhydrous ethanol and deionized water for 4 times and then vacuum dry it. The final product is a functional additive.
[0028] The preparation method of the pretreated inorganic carrier is as follows: add a modifying liquid with a mass 6 times that of the inorganic carrier to a 0.02 g / mL inorganic carrier ethanol dispersion, and stir and react at a temperature of 55°C for 3 hours; after the reaction is completed, centrifuge the resulting components, wash the filter cake with anhydrous ethanol 4 times and then transfer it to a vacuum drying device, and finally vacuum dry it at a temperature of 55°C to obtain the pretreated inorganic carrier.
[0029] The preparation method of the inorganic carrier is as follows: zirconium oxychloride is put into an ethanol aqueous solution with a volume concentration of 65% at a solid-liquid ratio of 50 mg / mL, methyl cellulose with a mass of 1.5 times that of zirconium oxychloride and polystyrene microspheres with an average particle size of 5 μm with a mass of 0.35 times that of zirconium oxychloride are added, the pH is adjusted to 3.5, and the reaction is kept stirring at 45°C for 60 minutes; after the reaction is completed, the pH is adjusted to 5.6, and after aging at room temperature for 20 hours, the resulting components are centrifuged, dried and sintered at high temperature in sequence, and the final product is the inorganic carrier; wherein the high-temperature sintering temperature is set to 1150°C, and the sintering time is set to 2 hours.
[0030] The preparation method of the modified liquid is as follows: 3-aminopropyltrimethoxysilane is added to an ethanol aqueous solution with a volume concentration of 85%, and the mixture is mixed and stirred evenly to prepare a silane coupling agent aqueous solution with a concentration of 0.8 mol / L; then the pH thereof is adjusted to 3.6, and the mixture is mixed and stirred at a rate of 300 r / min for 35 minutes at room temperature, and the modified liquid is obtained after the stirring is completed. Example 3
[0031] An antibacterial LED-UV curing rotary red ink is composed of the following raw materials in percentage by weight: 25% 1,6-hexanediol diacrylate, 10% 3-methyl-4-phenylbenzophenone, 0.8% tris(N-nitroso-N-phenylhydroxylamine)aluminum salt, 2% polyethylene wax, 8% functional additives, 2.5% polyester polyamide copolymer, 15% litho red, 1.2% calcium isooctanoate, and the balance is a connecting material; wherein the connecting material is compounded by vinyl ester resin and lauryl acrylate of equal quality.
[0032] The preparation method of the functional additive comprises the following steps: Step 1, cyanuric chloride, pretreated inorganic carrier, N, N-diethylethylamine and mixed solvent are mixed in a mass ratio of 2.0:1:0.04:12, 2,6-dimethyl-2,6-octadienal is added in a mass of 0.2 times that of the pretreated inorganic carrier, the mixture is stirred evenly, and the mixture is stirred and reacted at a temperature of 55°C for 5 hours; after the reaction is completed, the resultant components are separated into solid and liquid, and the obtained filter cake is washed 5 times with anhydrous ethanol and deionized water respectively; then vacuum dried, and the obtained solid powder is stored and used for standby; wherein the mixed solvent is prepared by mixing DMF and anhydrous ethanol in a volume ratio of 3:1.
[0033] Step 2: Mix 1,3-benzenediol, solid powder, aluminum chloride and chlorobenzene in a mass ratio of 1.8:1:0.05:10 and stir evenly. After keeping warm and stirring for 40 minutes at 40°C, the reaction temperature is raised to 95°C, and the stirring reaction is continued for 8 hours before filtering. The filter cake is washed with anhydrous ethanol and deionized water for 5 times respectively and then vacuum dried. The final product is a functional additive.
[0034] The preparation method of the pretreated inorganic carrier is as follows: add a modifying liquid with a mass 10 times that of the inorganic carrier to a 0.03 g / mL inorganic carrier ethanol dispersion, and stir and react at a temperature of 60°C for 4 hours; after the reaction is completed, centrifuge the resulting components, wash the filter cake with anhydrous ethanol 5 times and then transfer it to a vacuum drying device, and finally vacuum dry it at a temperature of 60°C to obtain the pretreated inorganic carrier.
[0035] The preparation method of the inorganic carrier is as follows: zirconium oxychloride is put into an ethanol aqueous solution with a volume concentration of 70% at a solid-liquid ratio of 80 mg / mL, methyl cellulose with a mass twice that of zirconium oxychloride and polystyrene microspheres with an average particle size of 10 μm with a mass of 0.4 times that of zirconium oxychloride are added, the pH is adjusted to 3.8, and the reaction is kept stirring at 50°C for 80 minutes; after the reaction is completed, the pH is adjusted to 5.8, and after aging at room temperature for 25 hours, the resulting components are centrifuged, dried and sintered at high temperature in sequence, and the final product is the inorganic carrier; wherein the high-temperature sintering temperature is set to 1150°C, and the sintering time is set to 2 hours.
[0036] The preparation method of the modified liquid is as follows: 3-aminopropyltrimethoxysilane is added to an ethanol aqueous solution with a volume concentration of 90%, and the mixture is mixed and stirred evenly to prepare a silane coupling agent aqueous solution with a concentration of 1.0 mol / L; then the pH thereof is adjusted to 3.8, and the mixture is mixed and stirred at a rate of 500 r / min for 40 minutes at room temperature, and the modified liquid is obtained after the stirring is completed.
[0037] Comparative Example 1: The main difference between this example and Example 1 is that this example does not use 2,6-dimethyl-2,6-octadienal in the process of preparing solid powder.
[0038] Comparative Example 2: The main difference between this example and Example 1 is that this example uses an equal amount of inorganic carrier to replace the functional auxiliary agent. Performance Testing
[0039] The properties of the red ink samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 were tested as follows: Antibacterial performance test: Cut the paper printed with the red ink sample into a circular paper with a diameter of 7mm, and put it close to the surface dish coated with bacteria, and place it at a constant temperature of 37℃ for 24h, then measure the diameter of the inhibition zone on the surface dish, and test it in parallel 5 times, and take the arithmetic mean as the final result (unit: mm). The larger the inhibition zone, the better the antibacterial effect.
[0040] Wear resistance: Tested in accordance with GB1768-1979 standard.
[0041] Adhesion: Tested in accordance with GB 1720-1979 standard.
[0042] The obtained test data is recorded in the following table:
[0043] By comparing and analyzing the relevant data in the table, it can be seen that the rotary red ink provided by the present invention not only has excellent antibacterial properties, but also has excellent wear resistance, which effectively guarantees its quality and grade while also extending its service life to a certain extent. This shows that the antibacterial LED-UV curing rotary red ink provided by the present invention has a broader market prospect and is more suitable for promotion.
[0044] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0045] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An antibacterial LED-UV curing rotary red ink, characterized in that: The invention is composed of the following raw materials in percentage by weight: 20-25% of organic monomer, 8-10% of photoinitiator, 0.3-0.8% of tri(N-nitroso-N-phenylhydroxylamine)aluminum salt, 1-2% of polyethylene wax, 5-8% of functional additive, 1.5-2.5% of dispersant, 12-15% of red pigment, 0.6-1.2% of drying agent, and the balance is connecting material.
2. The antibacterial LED-UV curing rotary red ink according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: Step 1, cyanuric chloride, pretreated inorganic carrier, N, N-diethylethylamine and mixed solvent are mixed in a mass ratio of 1.5-2.0:1:0.02-0.04:8-12, 2,6-dimethyl-2,6-octadienal is added in a mass of 0.1-0.2 times of the pretreated inorganic carrier, and the mixture is stirred evenly and then kept stirred at a temperature of 45-55° C. for 3-5 hours; after the reaction is completed, the resultant components are separated into solid and liquid, and the obtained filter cake is washed with anhydrous ethanol and deionized water for 3-5 times respectively; then vacuum dried, and the obtained solid powder is stored and used for standby; wherein the mixed solvent is prepared by mixing DMF and anhydrous ethanol in a volume ratio of 2-3:1; Step 2: Mix 1,3-benzenediol, solid powder, aluminum chloride and chlorobenzene in a mass ratio of 1.3-1.8:1:0.03-0.05:7-10, stir evenly, keep stirring at 30-40°C for 30-40 minutes, then raise the reaction temperature to 90-95°C, continue to keep stirring for 5-8 hours, and then filter. Wash the filter cake with anhydrous ethanol and deionized water for 3-5 times, respectively, and then vacuum dry it. The final product is a functional additive.
3. The antibacterial LED-UV curing rotary red ink according to claim 2, characterized in that: The preparation method of the pretreated inorganic carrier is as follows: adding a modifying liquid whose mass is 5 to 10 times of the inorganic carrier to a 0.01 to 0.03 g / mL inorganic carrier ethanol dispersion, and stirring and reacting at a temperature of 50 to 60° C. for 2 to 4 hours; after the reaction is completed, centrifuging the resulting components, washing the filter cake with anhydrous ethanol for 3 to 5 times and then transferring it to a vacuum drying device, and finally vacuum drying it at a temperature of 50 to 60° C. to obtain the pretreated inorganic carrier.
4. The antibacterial LED-UV curing rotary red ink according to claim 3, characterized in that: The preparation method of the inorganic carrier is as follows: zirconium oxychloride is added into an ethanol aqueous solution with a volume concentration of 60-70% at a solid-liquid ratio of 30-80 mg / mL, methyl cellulose with a mass of 1.5-2 times that of zirconium oxychloride and polystyrene microspheres with an average particle size of 5-10 μm with a mass of 0.3-0.4 times that of zirconium oxychloride are added, and the reaction is stirred at a temperature of 40-50° C. for 50-80 minutes after the pH is adjusted to 3.2-3.8; after the reaction is completed, the pH is adjusted to 5.5-5.8, and after aging at room temperature for 20-25 hours, the resulting components are centrifuged, dried and sintered at high temperature in sequence, and the final product is the inorganic carrier.
5. The antibacterial LED-UV curing rotary red ink according to claim 3, characterized in that: The preparation method of the modified liquid is as follows: 3-aminopropyltrimethoxysilane is added to an ethanol aqueous solution with a volume concentration of 80-90%, and the mixture is mixed and stirred evenly to prepare a silane coupling agent aqueous solution with a concentration of 0.5-1.0 mol / L; then the pH value thereof is adjusted to 3.5-3.8, and the mixture is mixed and stirred at a rate of 200-500 r / min for 30-40 minutes at room temperature, and the modified liquid is obtained after the stirring is completed.
6. The antibacterial LED-UV curing rotary red ink according to claim 4, characterized in that: The high temperature sintering temperature is set to 1100-1150° C., and the sintering time is set to 1-2 hours.
7. The antibacterial LED-UV curing rotary red ink according to claim 1, characterized in that: The connecting material is compounded by vinyl ester resin and lauryl acrylate in a mass ratio of 1:0.8-1.
0.
8. The antibacterial LED-UV curing rotary red ink according to claim 1, characterized in that: The photoinitiator is selected from any one of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide, bis (2,4,6-trimethylbenzoyl) phenyl phosphine oxide, and 3-methyl-4-phenyl benzophenone.
9. The antibacterial LED-UV curing rotary red ink according to claim 1, characterized in that: The organic monomer is selected from any one of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate.
10. The antibacterial LED-UV curing rotary red ink according to claim 1, characterized in that: The drying agent is selected from any one of cobalt isooctanoate, zirconium isooctanoate and calcium isooctanoate.
Citation Information
Patent Citations
LED-UV (Light Emitting Diode-Ultraviolet) silk-screen printing ink composition and preparation method of ink composition
CN103045007A
LED-UV curing offset printing ink
CN112898817A
Zirconium oxide microspheres, architectural coating containing zirconium oxide microspheres and preparation methods of zirconium oxide microspheres and architectural coating
CN116199521A
Modified inorganic pigment, method for producing modified inorganic pigment sol, inkjet recording unit and method for producing inkjet recording unit
JP2009249430A
Modified nano-silica and method for preparing the same, pigment dispersion and photosensitive resin composition
US20150299501A1